Insertion of nanostructured titanates into the pores of an anodised TiO2 nanotube array by mechanically stimulated electrophoretic deposition. Issue 16 (5th April 2017) - Martins, Alysson S.; Harito, Christian; Bavykin, Dmitry V.; Walsh, Frank C.; V. Lanza, Marcos R.
Abstract : TiO2 nanotube (TiO2 NT) surfaces can achieve a high area surface and enhanced electrocatalytic properties. Abstract : TiO2 nanotube (TiO2 NT) surfaces can achieve a high area surface and enhanced electrocatalytic properties. One of the key challenges is the insertion of nanostructured titanates deeply into the pores of TiO2 NT. We describe the electrophoretic deposition (EPD) of two different titanates - nanosheets (TiNSs) and nanotubes (TiNTs) into the pores of TiO2 NT to produce controlled hierarchical surfaces. A sufficiently high applied cell potential and mechanical stimulation of the surface are important to incorporate TiNSs and TiNTs inside the pores of TiO2 NTs. The electrodes show improved hydrophobicity after deposition of titanates. The beneficial effect of a counter electrode equipped with a brush to avoid the accumulation of a thick outer layer on TiO2NTs is highlighted.